(untitled) (Journal of the College of Basic Education, 2023)
This research aims to identify the impact of the Knowledge Keys strategy on the collection of Arabic grammar among fifth grade pupils. The following null hypothesis was derived: "There is no statistically significant difference between the mean scores of the experimental group who study Arabic grammar with the Knowledge Keys strategy and the mean scores of the control group students who study the same subject using the traditional method in the post achievement test." She conducted equivalence between the students of the two research groups with the following variables: (the chronological age of the students calculated in months, the educational attainment of the parents, the degrees of previous achievement, the Raven IQ test) in the first semester of the academic year (2022-2023 AD), she formulated the behavioral goals for the subjects that she will study, and they were ( 53) a behavioral goal according to Bloom’s three levels (knowledge, understanding, application(. The researcher prepared daily teaching plans for the subjects of Arabic grammar that will be studied during the experiment, in light of the content of the textbook and the formulated behavioral goals. Consisting of (30) objective items with four alternatives, and after analyzing the results statistically using the t-test for two independent samples (for the achievement test), the results resulted in the superiority of the students of the experimental group that studied with the knowledge keys strategy over the students of the control group that studied in the usual way in Achievement test, and based on that, the researcher presented a number of recommendations and proposals that were mentioned in the fourth chapter.